Integration of environmental education into English writing lessons in a Malaysian Chinese Independent High School - Paramanathan, Tathisangayathry; Syed Abdullah, Sharifah Intan Sharina (Human Resource Management Academic Research Society, 2022)
Environmental education has a great importance in Malaysia as it helps students to be aware of the various environmental risks that exist. One of the main issues that people currently face is the deterioration of the environment on a global scale. Henceforth, this study aims to explore integration of environmental education into students’ English writing studies where they are expected to learn about the numerous environmental repercussions while also developing English skills. This study focuses on this approach at a Chinese Independent High School in Selangor, Malaysia. Given that it lends meaning to any culture and a variety of aspects in the realms of science, the arts, and commerce, this topic is crucial to study. The chosen research methodology is qualitative. Five participants who were recruited using a purposive sampling process were the subjects of semi-structured interviews to gather the qualitative data. Thematic data analysis revealed that critical and creative thinking ought to play a significant role in the learning process in the classroom. The study's conclusions imply that teachers should prepare lesson plans where environmental elements are embedded into the learning outcomes or objectives. They need trainings to improve skills in preparing appropriate materials and content as well as to hone their pedagogical skills to deliver lessons effectively.